Serum Vitamin D Level in Overweight Individuals and Its Correlation With the Incidence of Non-alcoholic Fatty Liver Disease - Qu, Y.-L; Song, Y.-H; Sun, R.-R; Ma, Y.-J; Zhang, Y (Physiological research, 2024)
In this study, we investigated the serum vitamin D level in overweight individuals and its correlation with the incidence of nonalcoholic fatty liver disease (NAFLD). Between May 2020 and May 2021, the Department of Gastroenterology at the People's Hospital of Henan University of Traditional Chinese Medicine treated a total of 321 outpatients and inpatients with NAFLD, who were included in the NAFLD group, while 245 healthy age- and gender-matched individuals were included in the control group. All the data were collected for the relevant indices, including fasting plasma glucose, total cholesterol, triglyceride, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, alanine transaminase, and 25-hydroxy vitamin D (25[OH]D. The patients with NAFLD were divided into the normal BMI group, the overweight group, and the obese group, according to the body mass index, and the 25(OH)D levels were compared between the different groups. Spearman's correlation analysis was performed to analyze the correlation between the serum 25(OH)D level and NAFLD. Regarding the serum 25 (OH)D level, it was lower in the NAFLD group than in the control group ([18.36 + 1.41] μg/L vs [22.33 + 2.59] μg/L, t = ?5.15, P<0.001), and was lower in the overweight group than in the normal group ([18.09 ± 5.81] μg/L vs [20.60 ± 4.16] μg/L, t = 0.26, P = 0.041). The serum 25(OH)D level was thus negatively correlated with the incidence of NAFLD in overweight individuals (r = 0.625, P<0.05). In conclusion, the level of 25(OH)D decreased in patients with NAFLD with increasing BMI (normal, overweight, obese). Keywords: Nonalcoholic fatty liver disease, Vitamin D.
Keywords: vitamin D; mužské pohlaví; Body Mass Index; Male; nealkoholová steatóza jater; Overweight; nadváha; China; Humans; Female; Non-alcoholic Fatty Liver Disease; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Čína; Vitamin D; Vitamin D Deficiency; studie případů a kontrol; nedostatek vitaminu D; Case-Control Studies; dospělí; incidence; Adult; index tělesné hmotnosti; Incidence